Effect of crystallographic anisotropy on phase transformation and tribological properties of Ni-rich NiTi shape memory alloy fabricated by LPBF. (January 2023) - Shi, Guangfeng; Li, Lunxiang; Yu, Zhenglei; Sha, Pengwei; Cao, Qing; Xu, Zezhou; Liu, Yuting; Guo, Yunting; Si, Jiashun; Liu, Jiabao
Graphical abstract: Highlights: The maximum tensile recoverable strain could reach 4.13 ± 0.16% at room temperature by optimizing the hatch spacing. The superelasticity of LPBF-fabricated NiTi alloy was crystallographic orientation-dependent. The highest compressive recoverable superelastic strain of 7.91 ± 0.14 % was achieved in compression. How the sliding friction mechanisms were attributed to superelasticity and the friction pairs under different crystallographic orientation was investigated in detail. Abstract: This article investigated the effects of crystallographic anisotropy on the microstructure, phase transformation and tribological properties of NiTi Shape memory alloy (SMA) fabricated by laser powder bed fusion (LPBF). The maximum tensile recovery strain of 4.13 ± 0.16% was obtained at room temperature by adjusting the hatch spacing. The contributions of metallurgical factors under different crystal orientations, such as active twinned correspondence variant pairs (CVP), Schmid factor, critical stress for the stress-induced martensitic transformation (SIMT), Yong's modulus and nanohardness to superelastic response and tribological properties was clarified through various building orientations (0°, 45°, 90°). The results indicated that the superelasticity of LPBF-fabricated NiTi alloy was crystallographic orientation-dependent. Sample 0° with a strong (0 0 1) texture possessed the highest recoverable superelastic strain of 7.91 ± 0.14%. We describe, in detail, how the sliding friction mechanisms such as delamination, adhesive and formation of iron base oxide layers were attributed to superelasticity and the friction pairs under different loading conditions and building orientations. This new understanding reveals how different LPBF-induced microstructures affect mechanical properties and wear, providing a powerful guide for the tribological design or application and tailoring the functional behavior in LPBF-fabricated Ni-rich NiTi alloy.